Realities and challenges for mission transformation in Sabu people - Widjaja, Fransiskus I. (HTS teologiese studies, 2022)
Christianity has existed for more than 167 years on the island of Sabu (East Nusa Tenggara). Even though the majority of Sabu people are Protestant Christians, in everyday life, the Sabu people still adhere to the Jingitiu religion’s local beliefs. The value of Christianity is still considered foreign in the appreciation of most people’s faith even though they have become Christians. This research aims to develop the contextualisation of the missiological paradigm in the social culture of the Sabu people in a transformative mission challenge. Furthermore, the method used is a descriptive and qualitative research approach. The results showed the following: (1) the church needs to develop contextual studies (in the light of the Bible) on the cultural understandings of the Sabu people; (2) there is a need to bring together the gospel and culture through traditional activities and (3) the church needs to be proactive in transforming the Sabu people’s traditions as a tool to deliver education, such as moral and ethical education.Contribution: This article aims to assist churches in adopting strategies for inculcating gospel values in the religious traditions and practices of the Sabu people. This approach is proposed to further develop the appreciation of faith through transformation according to gospel values as a support system for proclaiming the message of the Great Commission in transmitting relevant and contextual Christian messages to transform the culture and society of Sabu.